Association between dietary intake and risk of Parkinson’s disease: cross-sectional analysis of survey data from NHANES 2007–2016 - Liu, Ling; Shen, Qiuyan; Bao, Yi; Xu, Fang; Zhang, Dan; Huang, Hongyan; Tu, Liangdan; Xu, Yanming (Frontiers in Nutrition, 2023)
Background: While dietary factors have shown an association with Parkinson's disease (PD), the available data remains a subject of ongoing debate and controversy. Aim: We sought to evaluate potential relationships between dietary consumption of nutrients and micronutrients and risk of PD in a large sample. Methods: Cross-sectional data were retrospectively analyzed for 10,651 adults aged 40-80 years that had been collected in the US between 2007 and 2016 as a component of the nationwide National Health and Nutrition Examination Survey. Aspects of dietary intake were compared between those who reported having specific PD medication regimens or not when they completed the survey, and potential associations between diet and risk of PD were explored using binomial logistic regression. We employed Propensity Score Matching (PSM) to minimize the impact of potential confounding factors, thus enhancing the reliability of the results. Additionally, subgroup analysis based on gender and age was conducted to investigate these relationships. Results: Higher dietary intake of iron was linked to greater PD risk [odds ratio (OR) 1.065, 95% confidence interval (CI) 1.019-1.114, p = 0.006], whereas risk decreased with higher intake of vitamin K (OR 0.999, 95% CI 0.998-1.000, p = 0.024) or vitamin C (OR 0.998, 95% CI 0.996-0.999, p = 0.039). Even after applying PSM, the connection between dietary iron intake and dietary vitamin C intake with PD risk remained substantial. Subgroup analysis results revealed a significant positive association between dietary intake of iron from food and the PD risk, which was evident among individuals under 60 years of age and among males. Conclusions: The intake of micronutrients can influence risk of PD, which should be verified and explored further in prospective samples with other dietary habits and ethnic backgrounds.